Antifungal Activity Test on α-guaiene Patchouli Oil Against Aspergillus niger and Candida albicans - Zhaqqu Ilham Alhafidz; Sarifah Nurjanah; Tita Rialita (Fakultas Teknologi Industri Pertanian, 2022)
Patchouli oil is composed by several component fractions with various benefits. The α-guaiene is one of the components of patchouli oil, which is thought to have antifungal activity. This study aimed to determine the antifungal activity of fraction I from patchouli oil fractionation containing 38,8% α-guaiene against Aspergillus niger and Candida albicans ATCC 7102 that affects human health. This research was an experimental study using the well diffusion method to determine the diameter of the inhibition. The treatment applied was the differences in the concentration level of fraction 1 patchouli oil (20%; 40%, 60%; 80% and 100%) and a positive control of ketoconazole 2% and a negative control of n-hexane. This study indicated that fraction I patchouli oil has antifungal activity. The diameter of the inhibition formed was directly proportional to the increase in the concentration of the test substance. The average diameter of the greatest inhibitory was obtained from the 100% concentration treatment for both fungi. The average diameter of inhibition in A. niger is 2.82 mm, while C. albicans is 7.69 mm. Ketoconazole 2% produced an average inhibitory diameter of 20.78 mm for C. albicans and 32.28 mm for A. niger, while n-hexane did not produce an inhibition zone.